The effect of time interval between antenatal corticosteroid administration and delivery on outcomes in late preterm neonates born to mothers with diabetes: a retrospective cohort study - Li, Xiaoyu; Zhang, Jing; Hao, Qingfei; Du, Yanna; Cheng, Xiuyong (Frontiers in Pediatrics, 2023)
Objectives: To investigate whether the time interval between antenatal corticosteroids (ACS) and delivery influences the neonatal outcomes in late preterm neonates (34+0–36+6 weeks) born to mothers with diabetes. Study design: This retrospective cohort study included women with any type of diabetes delivered from 34+0 to 36+6 weeks’ gestation. Cases were stratified into the following groups based on the time interval from the first dose of corticosteroids administration to delivery: <2, 2–7, and >7 days. Women who were not exposed to ACS served as the control group. Primary outcomes included the incidences of neonatal hypoglycemia and respiratory distress syndrome (RDS)/ transient tachypnea of the Newborn (TTN). Multivariate logistic regression was used to assess the relationship between the time interval and neonatal outcomes, as well as to adjust for potential confounders. Results: A total of 636 parturients were enrolled in the study. Of those, 247 (38.8%) delivered within 2 days after ACS administration, 169 (26.6%) delivered within 2–7 days of ACS administration, and 126 (19.8%) delivered at ＞7 days from ACS administration. Baseline characteristics such as type of diabetes, methods of glycemic control, PPROM, placenta praevia, cesarean delivery, indication for delivery, percentage of LGA, birth weight and HbA1c in second or third trimester were significantly different among the four groups. Multivariate analysis showed no statistically significant difference in the incidences of primary or secondary neonatal outcomes between the case groups and the control group. Conclusions: ACS treatment was not associated with neonatal hypoglycemia and respiratory outcomes of late preterm neonates born to diabetic mothers, regardless of the time interval to delivery.